Resilience of regionalism in Latin America and the Caribbean : development and autonomy - Rivarola, Andres; Briceno Ruiz, Jose (Basingstoke : Palgrave Macmillan, 2013)
'Regionalization has become a central issue in national and international debates since the end of the cold war. Yet, when local contributions to regionalism are considered, these are generally related to areas related to philosophy, identity and literature, rather than political economy. Addressing this vacuum, the authors of this volume argue that autochthonous ideas matter. Covering macro-regional and sub-regional outlooks, as well as presenting particular national perspectives concerning regionalist thinking, the contributors consider issues of regionalism where economics, political science and international relations come together' -Back cover.
Introduction : regional integration : linking past and present / Andr Rivarola Puntigliano and JosBrice-Ruiz -- Geopolitics and integration : a South American perspective / Andr Rivarola Puntigliano -- Regional integration in the inside trends of Latin American dependency thinking / Angel M. Casas-Gragea -- The Caribbean : regional unity in a context of diversity / JosBricen{u4BED}Ruiz -- Central America : in search of lost unity / Rodrigo P{u2865}z Montalb -- The Andes : a long tradition of thought and practice about regional integration / JosBricen{u4BED}Ruiz -- Latin American integration : a Mexican perspective / Mario V{u287A}quez Olivera and Fabi Campos Herndez -- Latin American integration : a Brazilian view / Clodoaldo Bueno, Tullo Vigevani and Haroldo Ramanzini J{u2D6E}ior -- Foreign policy and regional integration in Argentina : a long and winding road / Andr Rivarola Puntigliano and Miguel Angel Barrios -- Conclusion : about the endurance of Latin American regionalism / Andr Rivarola Puntigliano and JosBricen{u4BED}Ruiz.
Includes bibliographical references and index.
Keywords: Regionalism -- Latin America; Regionalism -- Caribbean Area; Latin America -- Foreign relations -- 1980-; Latin America -- Politics and government -- 1980-